RELAX and FIRMNESS: The Combination of Muscle Relaxation with Botulinum Toxin and Collagen Biostimulation with Calcium Hydroxyapatite for the Treatment of the Cervical Region - Faria GE; Palo JS; Torres AR; Machado AC; Boggio RF (Dove Medical Press, 2023)
Gladstone EL Faria, Juliana S Palo, Andre R Torres, Ana CHR Machado, Ricardo F Boggio Cosmiatry Department, Instituto Boggio, São Paulo, SP, BrazilCorrespondence: Gladstone EL Faria, Cosmiatry Department, Instituto Boggio, Rua Cincinato Braga nr 37. 8 floor, São Paulo, SP, 01333-011, Brazil, Email gladstonefaria@hotmail.comIntroduction: There are several therapeutic modalities for neck rejuvenation, especially calcium hydroxylapatite. Botulinum toxin, by relaxing the mm. platysma, also provides improvement in facial contour. Combination treatments for this region are usually recommended as they offer better results.Objective: This study evaluated the efficacy and safety of the joint dilution of both products (Relax and Firmness - RF), applied in the same device, based on the treatment in the topography of the platysma muscle, ie, starting from the lower third of the face and extending to the neck.Methods: Prospective, blinded, controlled study with 10 participants randomly assigned to RF and 5 in the control group (treated with CaHA only). Results were recorded through the Vectra platform and subjectively evaluated through the GAIS scale by participants and blinded evaluators. Objective analysis was performed using corneometry. Times evaluated: pre-treatment, 30 and 90 days. Considered statistically significant when p< 0.1.Results: 100% of the RF group reported "excellent improvement" at D30 and 30% at D90. In the control group, 100% reported "very improved" at D30 and 20% rated "excellent improvement" at D90. A higher and earlier satisfaction rate was observed in the RF group. No difference in corneometry was found between the groups at D30. At D90, the control group had a mean increase of 0.24 versus 5.17 in the RF group (p-value=0.089*). When we analyzed the percentage variation from baseline, the control group was stable, while the RF showed a mean increase of 8.89% (p-value=0.062*).Discussion: We demonstrated the safety and effectiveness of the association of both products, diluted and applied together through microcannulas. Minimization of punctures, patient comfort, and technique based on the anatomy of the platysma muscle underlie the technique. High rates of early satisfaction due to botulinum toxin (Relaxation) and late satisfaction due to CaHA (Firmness).Keywords: calcium hydroxylapatite, botulinum toxin, rejuvenation, neck, platysma muscle